2015
DOI: 10.1111/jth.12814
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation markers and their trajectories after deep vein thrombosis in relation to risk of post‐thrombotic syndrome

Abstract: Summary. Background: Post-thrombotic syndrome (PTS) is a frequent chronic complication of deep vein thrombosis (DVT). Objective: In the BioSOX study, we investigated whether inflammation markers predict the risk of PTS after DVT. Methods: We measured C-reactive protein (CRP), ICAM-1, interleukin (IL)-6, and IL-10, at baseline, and 1 month and 6 months after a first proximal DVT, among 803 participants in the SOX trial. Participants were prospectively followed for 24 months for development of PTS. Results: Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 51 publications
5
81
0
2
Order By: Relevance
“…Regarding known and possible factors associated with PTS, including older age, higher BMI, increased D-dimer levels and elevated CRP, the current study is consistent with most reports [3,5,16,[32][33][34][35]. Contrary to a few studies [3,7,9,34], we identified isolated and unprovoked DVT as an independent predictor of PTS, which is likely to be due to a close association of this type of VTE with proximal DVT in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding known and possible factors associated with PTS, including older age, higher BMI, increased D-dimer levels and elevated CRP, the current study is consistent with most reports [3,5,16,[32][33][34][35]. Contrary to a few studies [3,7,9,34], we identified isolated and unprovoked DVT as an independent predictor of PTS, which is likely to be due to a close association of this type of VTE with proximal DVT in our study.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have shown that PTS is closely associated with systemic inflammation and subsequent tissue remodeling and fibrosis [5,16]. Given reports on unfavorable clot properties in inflammatory states [10,11], we hypothesized that a prothrombotic clot phenotype is associated with a future risk of PTS.…”
Section: Introductionmentioning
confidence: 98%
“…Rabinovich et al . found that inflammation markers such as ICAM‐1 predict the risk of post‐thrombotic syndrome after DVT. Second, conditions that increase bacterial translocation have been implicated in the development of VT through higher circulating levels of lipopolysaccharide (LPS) along with increased expression of Toll‐like receptor 4 (TLR‐4), an innate immune receptor that is responsible for LPS recognition .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that patients with PTS had higher levels of markers of inflammation such as C-reactive protein, intercellular adhesion molecule-1 and interleukin 6 than those who do not develop PTS. 13,29,30 To our knowledge, to date no trial has been conducted to assess the effectiveness of anti-inflammatory drugs per se to prevent PTS. Regarding fibrinolysis, high D-dimer levels at various time points after DVT are associated with increased risk of PTS.…”
Section: Modifiable Risk Factorsmentioning
confidence: 97%